THE IMPACT OF RAHAYU MARKET ACTIVITY ON THE PERFORMANCE OF IMAM BONJOL STREET IN DENPASAR - I Made Agus Ariawan; I Gusti Raka Purbanto; Ni Putu Delima Yogeswari Saraswati (Jurnal Ilmiah Teknik Sipil, 2024)
Jalan Imam Bonjol is a road section located in the West Denpasar sub-district, precisely in the Pemecutan Klod area there is Rahayu Market which has activities in the morning. Activities in this market will indirectly reduce the performance of the section because there are large roadside obstacles. This study was conducted to determine how the performance of the section that occurs on the Imam Bonjol section with and without market activity followed by the impacts that occur. This research includes primary data collection to obtain road geometric values, vehicle volumes, and roadside obstacles, as well as speed (spot speed). The data obtained were analysed using the MKJI 1997 method. The results of the analysis of the performance of road sections in the presence of market activities in two conditions where the traffic volume for hourly conditions at peak times has Q of 1857.35 smp/hour, C of 2946.806 smp/hour, DS 0.63, V 23.92 km/hour with level of service F. While for the peak hour the side obstacle has Q of 690.15 smp/hour, C of 2626.501 smp/hour, DS worth 0.26, V of 19.2 km/hour with level of service F. The performance of the road section without the market obtained Q of 1846.2 smp/hour, C of 3203.05 smp/hour, DS worth 0.58, V of 36.8 km/hour with level of service C. Comparison of road section performance for traffic volume increased 1% and decreased 63% than without market, capacity decreased 8% and 18% than without market, degree of saturation increased 9% and decreased 55% than without market, speed decreased 35% and 48% than without market.